Analisis Semiotika Roland Barthes dalam Rubrik Sastra di Radar Madura - Moh Muhyi Rizal; Ainur Rahman; Ria Kasanova (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This study aims to describe denotative meanings, reveal connotative meanings, and analyze the process of myth formation in literary works published in the Radar Madura Literature Column using Roland Barthes' semiotic theory. This research employs a descriptive qualitative method with primary data sources consisting of five poems published in the Radar Madura Literature Column during the March-September 2025 period, namely Powasa Sakolana Kalbhu, Perempuan Pesisir, Melepas Angin Sakal Mengiringi Perjalanan, Sagara: Dialog Cinta, and Sanja'na. Data collection techniques were carried out through documentation and document analysis. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that denotative meanings are dominated by symbols of coastal life such as the sea, boats, waves, nets, sails, and wind. The connotative meanings found describe the struggle for life, hope, self-discovery, steadfastness, and religious values of the Madurese people. Meanwhile, the myth meanings show the construction of the cultural identity of the Madurese people who are known as religious, hardworking, resilient, and have a strong attachment to maritime culture. The research findings indicate that literary works in the Radar Madura Literature Column not only function as a medium for aesthetic expression but also as a means of representing local culture.